Proactive Eavesdropping With Adaptive Full-Duplex Jamming-Helping Method for Infrastructure-Free Relay Networks - Young-Jun Yoon; Wanjei Cho; Seongwook Lee; Jong-Ho Lee; Jiho Song; Seong-Cheol Kim (IEEE Access, 2023)
With the emergence of advanced communication technologies such as infrastructure-free communication networks, the need for proactive eavesdropping which can constantly monitor and intervene in the communication network is growing. In response to those demands, we study proactive eavesdropping in the general infrastructure-free communication scenario where the legitimate eavesdropper has to monitor a suspicious communication link without the aid of other nodes. Particularly, to enhance proactive eavesdropping performances, we propose the adaptive full-duplex jamming-helping method in which the legitimate eavesdropper selects the best operating mode adaptively depending on the channel conditions unlike conventional studies where the behavior of the monitor node was predetermined. Moreover, we design the optimal power scheme for the proposed method to maximize the eavesdropping rate while minimizing total power consumption of the legitimate eavesdropper simultaneously. In the process, we classify the channel conditions into several mutual exclusive cases to simplify the optimization problem, and present the optimal solution in closed form for each case. Finally, it is verified through simulation results that the proposed method is superior in terms of both the eavesdropping rate and the outage probability than other benchmark methods.